Patterned dextran ester films as a tailorable cell culture platform. (15th January 2021) - Tchobanian, Armen; Ceyssens, Frederik; Cóndor Salgado, Mar; Van Oosterwyck, Hans; Fardim, Pedro
Graphical abstract: Highlights: Dextran palmitates produce moderately hydrophobic films with low nano-roughness. The films are suitable for patterning via thermal nanoimprint lithography (T-NIL). T-NIL patterning introduces defined regions with increased apparent contact angles. The model platform allows guidance of cell adhesion and multicellular arrangements. T-NIL patterned polysaccharides are used as a biological substrate for the first time. Abstract: The elucidation of cell-surface interactions and the development of model platforms to help uncover their underlying mechanisms remains vital to the design of effective biomaterials. To this end, dextran palmitates with varying degrees of substitution were synthesised with a multipurpose functionality: an ability to modulate surface energy through surface chemistry, and an ideal thermal behaviour for patterning. Herein, dextran palmitate films are produced by spin coating, and patterned by thermal nanoimprint lithography with nano-to-microscale topographies. These films of moderately hydrophobic polysaccharide esters with low nanoscale roughness performed as well as fibronectin coatings in the culture of bovine aortic endothelial cells. Upon patterning, they display distinct regions of roughness, restricting cell adhesion to the smoothest surfaces, while guiding multicellular arrangements in the patterned topographies. The development of biomaterial interfaces through topochemical fabrication such as this could prove useful in understanding protein and cell-surface interactions.